Global Tax Volunteer Effectiveness in Enhancing Annual Return Services: Efektivitas Relawan Pajak Global dalam Meningkatkan Pelayanan SPT Tahunan - lindah cahyani; Herman Ernandi (Academia Open, 2024)
This study analyzes the effectiveness of tax volunteer student services in assisting individual taxpayers with Annual Tax Return Reporting, particularly forms 1770S and 1770SS, at the West Sidoarjo Pratama Tax Service Office using the e-filing system. Utilizing a qualitative approach through observations, interviews, and documentation, and ensuring data validity with triangulation, the research finds that the involvement of student volunteers significantly enhances the e-filing process's efficiency and compliance with regulations. The study highlights the need for continuous, structured tax education and suggests improvements in volunteer training and taxpayer awareness to further streamline tax reporting processes. Highlight: Effective Assistance: Volunteers improve e-filing efficiency for individual taxpayers. Regulation Compliance: Services align with PER-12/PJ/2021 tax regulations. Continuous Education: Ongoing tax education is essential for volunteers and taxpayers. Keyword: Tax Volunteers, Annual Tax Return, E-Filing, Individual Taxpayers, Tax Education